Capillas sepulcrales y lugares de enterramiento de la nobleza limeña - Patrucco Núñez-Carvallo, Sandro (2010)
This article is part of an ongoing exploration of attitudes towards death among the nobility of eighteenth-century Lima. It analyzes the conspicuous consumption evident in private chapels and burial crypts as a component of elite social status.